The household economic impact of Rheumatic Heart Disease (RHD) in South Africa - Oyebamiji, Oyeleke (Department of Public Health and Family Medicine, 2019)
Background: Rheumatic heart disease (RHD) remains a major public health concern in African countries due to the high rates of complications such as atrial fibrillation, stroke, infective endocarditis, and heart failure, all of which can result in premature death. In 2015, RHD was estimated to affect 33 million people globally and resulted in at least 320,000 deaths, nearly all of which were in low and middle-income countries. Comparing to other non-communicable diseases (NCDs), RHD imposes economic burden on households that if measures are not in place to mitigate this, it can impoverish such household. However, there are several literatures on the intergenerational economic consequences of other chronic diseases. But, there is no study regarding the household economic of RHD. This mini-dissertation sets out to estimate the household economic impact of RHD. Methods: This study was a follow-on study from the Global Rheumatic Heart Disease Registry (REMEDY), which was a multi-center, international, hospital-based prospective registry of patients with RHD. It was designed as a cohort study to document the disease characteristics and outcomes of individuals with RHD across many countries. We recruited participants in the REMEDY study who were resident in Cape Town and received care at Groote Schuur Hospital (GSH). This study made use of patient and household member surveys to estimate the economic consequences of RHD among households in which REMEDY participants reside. REMEDY registry participants (index cases), their caregivers, and other household members were considered as respondents. 100 REMEDY participants receiving care at GSH was sampled. This sample size was chosen to balance feasibility and precision and to align with a parallel study of the cost of RHD to the health system that aimed to sample medical records from the same 100 REMEDY participants. Patient and household data collection was carried out between September 2017 to December 2017. Direct costs, indirect costs, and the downstream economic behaviors (coping strategies) that lead to medical impoverishment and other consequences were estimated. Cost of illness (COI) was used to assess the effect of ill-health and health-related expenditure on the consumption possibilities of households. Direct costs comprise both medical and nonmedical costs, which may include both the financial cost of resources as well as opportunity costs (e.g., of capital items). Human capital approach was used to calculate indirect cost. Implicit in the human capital approach is the assumption that changes in health status of household members can be reflected by losses in productivity, and losses in income generation. Productivity losses was estimated using the new South Africa minimum wage rate per month as proxy. Coping was estimated with the direct costs (e.g., borrowing from friends or relatives, or taking out formal loans) or indirect costs (e.g., intra-household labor substitution) and can be cost prevention strategies (e.g., ignoring illness, non-treatment) to cost management strategies (e.g., borrowing, selling assets, or labor substitution). Economic costs were valued in United State dollar (USD) converted from South African rand (ZAR) in 2017. Results: Direct medical cost was estimated to ZAR 0, because all patients were exempt from medical fees. Total direct non-medical cost for outpatient and inpatient visits was estimated to be ZAR 27,000 (USD 2000) and 29,000 (USD 2200) (respectively) over 302 and 74 encounters (respectively), an average of ZAR 270 (USD 20) and ZAR 290 (USD 22) per patient (respectively). Indirect costs incurred over the 302 outpatient encounters and 74 hospital admissions were estimated to be ZAR 41,000 (USD 3100) and ZAR 26,000 (USD 1900) (respectively), an average of ZAR 410 (USD 31) and ZAR 260 (USD 19) per patient. Direct cost had a very high impact on the household and they were compelled to adopt coping. Households observed in the study recorded that seventeen percent of households took out loans at an average of ZAR 1200 (USD 91) per loan (range ZAR 100 to ZAR 7000) (range USD 7 to 500). Fifteen percent received financial gifts at an average of ZAR 800 (USD 61) per gift. Two percent sold assets valued at ZAR 5600 (USD 120) on average. Five percent engaged in multiple coping strategies. Also, HH had to cope with indirect cost of illness as 15% of household caregivers changed jobs and 10% worked extra hours. About 4% of household members dropped out of school. Four percent adopted more than one coping strategy. A considerable share of participants reported that they had reduced education to take care of the affected patient. Most of the caregivers of patients with RHD were spouses and children, and 6 % were heads of household. The total cost of RHD to the average affected household is valued at about ZAR 1600 annually. In total, the overall annual economic impact of RHD in this sample of 100 households affected by RHD was estimated at ZAR 160,000 (USD 12200) (ZAR 1600 per household) (USD 120), representing 4.4% of annual household income or 4.9% of annual household expenditure patient spending that exceeded 10% threshold was estimated to be 8% and increasing the threshold to 40 % of non- food expenditure reduced the prevalence of catastrophic spending to 4%. Conclusions: The economic impact of RHD in South Africa is substantial despite government efforts to provide free care. The total cost of RHD to the average affected household is valued at about ZAR 1600 annually. A broader and more robust range of social policies will be required to mitigate non-medical and indirect costs and reduce distortions in household economic activity.